Into the Wild, Out of the Woods: A Systematic Case Study on Facilitating Emotional Change - Gunst, E. (International journal of offender therapy and comparative criminology, 2019)
Cognitive and behavioral treatment programs for individuals who have committed sexual offenses (ISOs) have shown significant but small effect sizes. A growing body of research points toward the importance of difficulties in affect regulation (AR) as a risk factor for sexual recidivism. On this basis, it seems important to target difficulties in AR in treatment. The current systematic case study investigates the potential contribution of emotion-focused therapy (EFT) to changing problematic AR in ISOs. Kevin was a high-risk offender with a traumatic history who met the diagnostic criteria of pedophilic and borderline disorders, with serious AR difficulties. Self-report outcome measures, observation measures, and a biomarker were used to track changes in AR, psychological symptoms, and distress during baseline (Phase A); treatment as usual (Phase B); treatment with an EFT component added (Phase C); and follow-up (Phase A). Statistically significant change was found in AR, psychological symptoms, and distress during treatment (Phase B + C); however, it is not possible to attribute these changes causally to EFT. An examination of the qualitative process data provides deeper insights into how the client reacted to specific EFT interventions. Verbatim clinical vignettes are included to clarify key interventions, hindrances, and mechanisms of change. This study provides preliminary support for the role of therapy to facilitate emotional change in ISOs.